BENEFITS OF GIVING (A BOOK REVIEW USING ISLAMIC PERSPECTIVE) - Arraiyyah, M. Hamdar (Center for Research and Development of Religious Literature and Heritage, 2015)
This writing is a book review. It discusses a book entitled Give and Take. The book introduces a new approach to success. It makes three categories of people in doing interaction or communication. They are takers, matchers, and givers. The writer of the book, Adam Grant, explains the principles and characteristics of each category. He shows a lot of facts to prove that being a giver brings benefits for people and the doer as well. The objects of giving here comprise different kinds help like wealth, ideas, knowledge, skills and information. Therefore, he motivates people to become givers. In this connection, the reviewer would like to show that Islamic religion also motivates its followers to give helps to others. Though, there are some similarities and differences between the benefits of giving mentioned in the book and the verses of the Holy Qur?an and the sayings of Prophet Muhammad Peace be upon him.